2005
DOI: 10.1002/anie.200502686
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous FeIVO: Spectroscopic Identification and Oxo‐Group Exchange

Abstract: Figure 1. Mössbauer spectra of a sample at 4.2 K containing 250 mm Z, prepared by the rapid freeze-quench technique (see Supporting Information). The solid lines (red for Z, representing ca. 50 % of total Fe) are simulations based on Equation (2). The contribution from [Fe(H 2 O) 6 ] 3+ is shown in blue. We found the following parameters for Z: D = 9.7(7) cm À1 , A x /g n b n = A y / g n b n = À20.3(3) T, DE Q = À0.33(3) mm s À1 , d = 0.38(2) mm s À1. For the 8.0-T spectrum, the theoretical curves for Z and [F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
297
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 338 publications
(332 citation statements)
references
References 26 publications
34
297
1
Order By: Relevance
“…For the analysis, parameters determined from the 40-mT spectrum (␦ and ⌬E Q ) were kept constant, and it was assumed that the A-tensor is axial. Similar spectra were observed for J in TauD (43) and a high-spin Fe(IV)-oxo model complex (31), but the magnetic splitting in the spectra of the P4H complex is smaller than that for J in TauD. The diminished splitting ref lects smaller internal magnetic fields and is a consequence of the larger zero-field splitting parameter, D. Neese and colleagues (42,44) showed that the magnitude of D is primarily governed by the energy separation between the S ϭ 2 ground state and the low-lying …”
Section: Fq Mö Ssbauer-spectroscopic Evidence For Accumulation Of a Psupporting
confidence: 74%
See 1 more Smart Citation
“…For the analysis, parameters determined from the 40-mT spectrum (␦ and ⌬E Q ) were kept constant, and it was assumed that the A-tensor is axial. Similar spectra were observed for J in TauD (43) and a high-spin Fe(IV)-oxo model complex (31), but the magnetic splitting in the spectra of the P4H complex is smaller than that for J in TauD. The diminished splitting ref lects smaller internal magnetic fields and is a consequence of the larger zero-field splitting parameter, D. Neese and colleagues (42,44) showed that the magnitude of D is primarily governed by the energy separation between the S ϭ 2 ground state and the low-lying …”
Section: Fq Mö Ssbauer-spectroscopic Evidence For Accumulation Of a Psupporting
confidence: 74%
“…This mechanism has served well as a general working hypothesis for the mechanisms of all of the ␣KG-dependent dioxygenases: extensive studies on several family members, and inorganic models thereof have failed to reveal significant inconsistencies (1)(2)(3)(26)(27)(28)(29)(30)(31). However, the first direct evidence for any of the several oxidized iron intermediates invoked in this mechanism came relatively recently, with the detection by stopped-flow (SF) absorption and freeze-quench (FQ) Mössbauer spectroscopies of two transient states in the catalytic cycle of taurine:␣KG dioxygenase (TauD) (see Scheme 1) (32).…”
mentioning
confidence: 99%
“…One of the first crystal structures with a terminal Fe IV ¼ ¼oxo indeed was intermediate spin, as indicated by M€ ossbauer spectroscopy. [18] High-spin biomimetic complexes remain rare with very few examples, [20][21][22][23] the set of which was very recently extended by a complex with a trigonal pyrrolide platform. [19] Que and coworkers [24] recently also reported a Fe(IV)-oxo-hydroxo species, starting from a highspin Fe II (benzilate) complex.…”
Section: Metal-oxo Species and Exchange-enhanced Reactivitymentioning
confidence: 99%
“…[54][55][56][57] Important milestones in this area are the first report of the spectroscopic [77] and structural [78] characterisation of intermediate-spin non-heme ferryl model complexes as well as a detailed mechanistic study of the a-keto-acid-dependent enzyme TauD with a high-spin ferryl active site. [79][80][81][82] Especially interesting, therefore, are the observations of high-spin low-molecular-weight ferryl species [83][84][85][86][87] and the proposal of catalytically active intermediate-spin dihydroxo-iron(IV) complexes. [84] An important observation is that ferryl complexes can be trapped in pure water, prepared from the Fe II precursor and H 2 O 2 under typical Fenton conditions.…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 99%